Exploring the multi-scale ecological consequences of stoichiometric imbalance using an agent-based modeling approach - Bradley, LM; Duvall, Ethan S.; Akinnifesi, Olufemi J.; Novotná Jaroměřská, Tereza; Junker, James R.; Wong, Esther (Frontiers in Ecology and Evolution, 2025)
Despite living in a nutritionally heterogeneous world, consumers maintain a relatively strict elemental homeostasis. As a result, consumers often face an elemental imbalance between what they ingest and what is required for their growth, maintenance, and reproduction. Here, we attempt to unite concepts from three complementary frameworks used to study these imbalances—Ecological Stoichiometry Theory (EST), Dynamic Energy Budget (DEB) theory, and Nutritional Geometry (NG)—within an agent-based modelling (ABM) approach. Specifically, we developed a two-reserve DEB model within the ABM that tracks elemental intake, storage, and release in individual consumers across space and time, all while integrating energetic trade-offs and simulating behavioral responses to stoichiometric mismatch. This approach provides a platform to study the effects of stoichiometric imbalances on populations with individuals that have heterogeneous traits, and on feedbacks between consumer populations and environmental nutrient cycling. We demonstrate the utility of this approach through a case study of snowshoe hares (Lepus americanus) balancing carbon and nitrogen intake in a nitrogen-limited landscape. Our case study demonstrates how heterogeneity in resource stoichiometry, and the ability for consumers to respond to such heterogeneity under nutrient limitation, can have variable effects on population dynamics and consumer nutrient cycling. Ultimately, our ABM is able to capture how stoichiometric mismatches faced at the individual level can drive emergent ecological outcomes through the collective impacts on the population. While the intricacy of our model ensures ample room for further improvements and expansions, we hope this user-friendly tool will enable practitioners of EST, DEB, and NG to test new hypotheses, guide experimental and field research, and advance theoretical development.